K fenomenológii dotýkania a filozofii lásky (To phenomenology of touching and philosophy of love) - Miloš Kriššák (Ostium, 2009)
A starting point of an essay is Merleau-Ponty’s ontology of corporality. Merleau-Ponty reformulates a problem of erotic perception which cannot be founded in intentionality of concioussness but in that of body. Later, in search for the ontology of corporality, he founds that we are open to the world as corporeal beings thanks to the order of Visibility, which is the essence of corporality. Second part of the essay challenges Merleau-Ponty’s idea of reversibility of seeing and touching. Under Lacanian consideration of ontogenesis of subjectivity, it is shown that the primordial world before visible and invisible is haptic world of corporeal being. Consecutively, this fact is drawn back to the idea of erotic perception as a relation to non-visible haptic body of the other that happens in and returns back to a realm before constitution of any meaning.